Visual engagement and comfort perceptions in pediatric patient rooms: A virtual reality and eye-tracking study using photographic stimuli - Haripriya Sathyanarayanan; Yueci Jiang; Luisa Caldas; Coye Cheshire (Computers in Human Behavior Reports)
Understanding how pediatric patient room design influences comfort and care perceptions is critical for improving healthcare environments. This study examines the visual engagement and subjective experiences of 23 children (8–17 years) and 21 parents using a Virtual Reality (VR) and eye-tracking approach with photographic stimuli of thirty-two pediatric acute care rooms. A mixed-methods framework integrates eye-tracking metrics, survey ratings, and qualitative feedback to analyze how specific design elements shape perceptions of comfort, care, and likeability.Findings reveal that younger children engage more with toys, artwork, and window views, indicating their role in providing distraction and emotional support. Older children prioritize furniture and personal items, reflecting a need for autonomy and personalization. Parents emphasize window views, room layout, and positive distractions, aligning with their focus on caregiving and emotional comfort. Across all groups, familiarity and personalization emerged as key contributors to comfort and care perceptions, reinforcing the importance of designing spaces that support emotional well-being.This study highlights the value of VR and eye-tracking methodologies in capturing real-time user engagement, providing evidence-based insights for pediatric healthcare design. The findings underscore the need for patient-centered, participatory approaches that address the diverse needs of pediatric patients and their families.